Analisa Keselamatan dan Kesehatan Kerja Menggunakan Metode HIRARC Pada Proses Produksi di Mesin Stamping (Studi Kasus di PT. XYZ) - Arief Wahyu Pamungkas; Agustian Suseno (Jurnal Ilmiah Wahana Pendidikan, 2022)
PT. XYZ is a company engaged in manufacturing with its main production results, namely automotive components. Although many efforts have been made by PT. XYZ to minimize accidents and diseases due to work, but the results are still not able to run optimally. This is shown by the still reports related to work accidents, one of which is in the stamping process area. The purpose of this study is to reduce the risk level of work accidents in the production area of stamping machines in PT. XYZ. The study used the HIRARC method to identify, assess and control risk. In production activities in stamping machines, 6 potential hazards were found with a percentage of each risk, namely 67% in the low risk category, 16% moderate risk), and 17% high risk. Recommended risk control in the form of administrative control with safety talk and rule making for workers who do not comply with PPE completeness while in the work area, as well as engineering engineering with the manufacture of covers on stamping machines.